PENERAPAN MODEL OUTDOOR LEARNING ACTIVITY DALAM PEMBELAJARAN IPAS UNTUK SISWA KELAS III DI SEKOLAH DASAR - Ficky Erina Diyas Fertiana; Dwi Anggraeni Siwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Outdoor Learning Activity model in Science and Social Studies (IPAS) learning for third-grade elementary school students and to identify supporting and inhibiting factors in its implementation. This research was conducted at SD Negeri 2 Sukomangu, Purwantoro District, Wonogiri Regency. The study employed a qualitative descriptive approach. Research subjects consisted of one third-grade teacher and 13 third-grade students. Data collection techniques included observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Outdoor Learning Activity model was carried out through planning, implementation, and evaluation stages. Students actively participated in observing, discussing, and presenting learning outcomes. The model increased students’ learning enthusiasm, participation, collaboration skills, and understanding of IPAS concepts through direct experiences. Supporting factors included the availability of a conducive school environment, teacher readiness, and students’ enthusiasm. Meanwhile, inhibiting factors included weather conditions, time limitations, and classroom management challenges during outdoor activities. Therefore, the Outdoor Learning Activity model can be used as an effective alternative learning model to create meaningful and contextual learning experiences in elementary schools.